A learner-led conference to enhance interdisciplinary social accountability education in healthcare: participant perspectives on engagement and educational experience (Canadian Medical Education Journal, 2025)
Implication StatementWe developed the Interdisciplinary Social Accountability Conference in Healthcare to address educational gaps and empower learners to advocate for healthcare needs. This conference aimed to strengthen social accountability competencies in students through three areas: (1) a learner-led planning model that promotes initiative-taking and leadership, (2) interactive sessions on locally relevant topics, and (3) a student research showcase to foster interdisciplinary dialogue. Survey findings demonstrated high engagement and positive experiences with cross-disciplinary networking. We encourage institutions to adopt similar learner-led initiatives, facilitating students to take an active role in shaping social accountability education and supporting attendees in gaining practical skills through workshops on locally-relevant issues. These initiatives will equip learners with the collaborative mindset and skills required to improve health outcomes in their communities.